Granulomatosis with polyangiitis presenting as otomastoiditis with nasopharyngeal and parotid lesions - Jacob G. Eide; Anisha B. Dua; Borislav A. Alexiev; Akihiro J. Matsuoka (Otolaryngology Case Reports, 2021)
A middle-aged woman presented with two months of left ear pain and hearing loss. She had previously been admitted to an outside hospital for left-sided otomastoiditis and was treated with antibiotics without resolution. After failing outpatient management with pressure equalization tube placement and developing new neck pain, she was admitted to the hospital to rule out meningitis. Lumbar puncture was normal and the patient started on broad-spectrum intravenous antibiotics. Computed tomography and magnetic resonance imaging showed persistent fluid in the left middle ear and mastoid without bony erosion as well as a mass in the left nasopharynx and right parotid gland. The patient did not improve and was taken for biopsy of masses and left tympanomastoidectomy. Multiple blood and tissue samples were negative for infection or malignancy. Ultimately, autoimmune labs were obtained showing elevated cANCA and serine proteinase 3 (PR3), consistent with granulomatosis with polyangiitis and she improved with steroid treatment. This is the first report of GPA with focal simultaneous involvement of the nasopharynx and parotid, which made the diagnosis challenging to establish.